Institutional deliveries in India's nine low performing states: levels, determinants and accessibility. Issue 1 (1st January 2021) - Saha, Ria; Paul, Pintu
ABSTRACT: Background: Despite the implementation of several national-level interventions, institutional delivery coverage remains unsatisfactory in India's low performing states (LPS), leading to a high burden of maternal mortality. Objective: This study investigates the levels, differentials, and determinants of institutional deliveries in LPS of India. The study also delineates a holistic understanding of barriers to delivery at health facilities and the utilization of the Janani Suraksha Yojana (JSY) specifically designed to improve maternal and child health of disadvantaged communities. Methods: A cross-sectional study was conducted using data from the National Family Health Survey (NFHS)-4, 2015–16. The study was carried out over India's nine LPS utilizing 112, 518 women who had a living child in the past five years preceding the survey. Bivariate and multivariate regression analysis techniques were used to yield findings. Results: Of the study sample, nearly three-quarters (74%) of women delivered in a health institution in the study area, with the majority delivered in public health facilities. The multivariate analysis indicates that women who lived in rural areas, belonged to disadvantaged social groups (e.g. Scheduled caste/tribes and Muslims), and those who married early (before 18 years) were less likely to utilize institutional delivery services. On the other hand, women's education, household wealth, and exposure to mass media were found to be strong facilitators of delivering in a health facility. Meeting with a community health worker (CHW) during pregnancy emerged as an important predictor of institutional delivery in our study. Further, interaction analysis shows that women who reported the distance was a 'big problem' in accessing medical care had significantly lower odds of delivering at a health facility. Conclusions: The study suggests emphasizing the quality of in-facility maternal care and awareness about the importance of reproductive health. Furthermore, strengthening sub-national policies specifically in underperforming states is imperative to improve institutional delivery coverage.